The Influence of Potential Loss Portfolio Ratio and PBH Investment Ratio on Bus ROA in Indonesia 2015 - 2022 - Nuriasari, Selvia; Rodoni, Ahmad; Pratiwi, Leni Nur (Al-Muhasib: Journal of Islamic Accounting and Finance, 2023)
The ratio of the portfolio of potential losses in profit-sharing financing to the mudharabah and musyarakah investment portfolio and the ratio of investment in profit-sharing financing to total financing is used to measure the results of Sharia bank investments in profit-sharing-based financing. It is known that from 2015 to 2022 the development of assets and disbursed financing (PYD) tends to decrease and in the following year increases, resulting in fluctuations in the two investment ratios. The fluctuation of two investment ratios is an interesting problem to research. This research is a quantitative descriptive study using PASW 18 which describes the results using figures with secondary data sources including the OJK Sharia Banking Statistics Report for 2015 - 2022 and the Monthly Financial Report of Sharia Banks. The research conclusion is that the investment ratio from 2015 to 2022 experienced fluctuations due to the decline in mudharabah financing and musyarakah financing at Sharia Banks.